Lama Fermentasi dan Konsentrasi Bunga Chamomile (Matricarica recutita) Terhadap Mutu Fisikokimia dan Organoleptik Teh Kombucha - Fahilah, Khoiriyah; Hartati, Fadjar Kurnia; Yuniati, Yuyun (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Kombucha is a health drink that has good benefits for the body, contains polyphenols and is antioxidant so it is said to be a functional drink. Chamomile positively contains flavonoid compounds, polyphenols, and tannins as antioxidants to ward off free radicals. The purpose of this study was to determine the effect of fermentation duration and concentration of chamomile flowers (Matricaria recutita) to produce kombucha drink with the best physicochemical and organoleptic quality. This study used a one-factorial Completely Randomized Design consisting of four treatments of a combination of fermentation duration (5 days and 7 days) and chamomile concentration (0.5% and 1%), each treatment was carried out three times. Parameters analyzed included color (L*a*b*), pH, antioxidant activity and organoleptic (taste, color, and aroma). The results showed that the length of fermentation and chamomile concentration had a significant effect on color (L*a*b*), pH, antioxidant activity and organoleptic parameters (taste and color). On organoleptic parameters (aroma) did not have a significant effect. The best treatment with antioxidant activity value of 67.09% in treatment F2C2 (7 days fermentation time and 1% chamomile concentration). The highest organoleptic quality was in the F1C1 treatment (5 days fermentation and 0,5% chamomile concentration).